‘Early planning makes for a good death’: residential aged care nurses’ views on caring for those in the last months of life - Priyanka Vandersman; Jennifer Tieman (BMC Nursing)
Abstract Background The residential aged care (RAC) sector provides care to a significant number of older people across frail and vulnerable years, all the way through to death. As such, palliative care, and considerations for end-of-life caring, need to be considered as core in aged care practice in Australia. Aim To explore how RAC nurses understand, describe, and provide care to people who are in the last months of life. Methods A qualitative descriptive research study design based on the secondary analysis of data collected as part of a larger study. Focus groups and semi-structured interviews were conducted with RAC nurses working in Australia using video conferencing software and telephone. Data collected was managed using the NVivo software and analysed using reflexive thematic analysis. Results Sixty-four participants from 14 RAC services across three Australian States took part in study. Four themes emerged from the analysis of the data, namely: (1) The last months of life have unique caring needs; (2) Identifying the last months of life is complex (3), Care provision is driven by task orientation, and (4) Good end-of-life care is acknowledged yet limited. Participants highlighted differences in the needs of older people experiencing gradual decline versus those in the terminal stage. Early discussions about death with families and residents were deemed valuable, but resource constraints limited the opportunities of quality one-on-one care. Conclusion Nurses see value in recognising early health decline and identifying residents nearing end-of-life, but workflow and resource limitations hinder their ability to engage effectively. Developing and implementing resources and processes to enable nurses to identify early decline and deliver timely, quality end-of-life care is imperative.